2016
DOI: 10.1097/pcc.0000000000000715
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Overload Is Associated With Late Poor Outcomes in Neonates Following Cardiac Surgery*

Abstract: Objective Acute kidney injury (AKI) is a severe complication of cardiac surgery associated with increased morbidity and mortality, yet AKI classification for neonates remains challenging. We characterized patterns of post-operative fluid overload (FO) as a surrogate marker for AKI and as a risk factor of poor post-operative outcomes in neonates undergoing cardiac surgery. Design Retrospective cohort study. Setting Single, congenital heart center destination program. Patients 435 neonates undergoing cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 36 publications
6
51
0
1
Order By: Relevance
“…For example, in a retrospective chart review of 80 children with mean ages 58.7 ± 73 months with respiratory failure, Arikan et al found that fluid overload of ≥15% was independently associated with longer hospital stay, longer duration of ventilation, and worse oxygenation index [66]. A recent retrospective study analyzed data from 435 neonates who underwent cardiac surgery with cardiopulmonary bypass and found that fluid overload of ≥16% was an independent risk factor for worse outcomes [67]. …”
Section: Management Of Aki In the Neonatementioning
confidence: 99%
“…For example, in a retrospective chart review of 80 children with mean ages 58.7 ± 73 months with respiratory failure, Arikan et al found that fluid overload of ≥15% was independently associated with longer hospital stay, longer duration of ventilation, and worse oxygenation index [66]. A recent retrospective study analyzed data from 435 neonates who underwent cardiac surgery with cardiopulmonary bypass and found that fluid overload of ≥16% was an independent risk factor for worse outcomes [67]. …”
Section: Management Of Aki In the Neonatementioning
confidence: 99%
“…Fluid overload and acute kidney injury are serious complications in children after congenital heart surgery, with a documented prevalence as high as 45%. 14 No consensus has been reached as to how to best prevent fluid overload or acute kidney injury or how to manage these conditions if they develop. Peritoneal dialysis appears as a reasonable strategy to help manage fluid removal and clearance from a physiological point of view, but limited data exist to demonstrate that this provides benefit when compared to fluid restriction and dieresis.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 Historically and currently, the prophylactic placement of a peritoneal dialysis catheter has depended on physician preference. 14,26 This decision is often based on thorough assessment of the likelihood that fluid overload or acute kidney injury may develop in the post-operative setting based on characteristics such as age, complexity of the congenital heart surgery, and duration of cardiopulmonary bypass. 27 Thus, disease severity or the perception of severity still appears to be the major factors for determining the use of peritoneal dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…En un estudio en el que se incluyeron más de 400 neonatos sometidos a cirugía cardíaca que presentaron LRA, se determinó que una sobrecarga de líquidos superior al 16 % estuvo asociada de manera estadísticamente significativa a mal pronóstico (mayor mortalidad, días de hospitalización y prolongación en días de asistencia respiratoria mecánica). 13 Estadío prerrenal: se recomienda la administración endovenosa de solución salina isotónica a razón de 10-20 ml/kg en una-dos horas. 14 IRA intrínseca: para los RN con oliguria o anuria, el aporte se limita a pérdidas insensibles más la eventual diuresis.…”
Section: Aporte Hídricounclassified